Hematological changes in descendants of animals irradiated in different doses - Stepanov, G.; Vastyanov, R.; Kostina, A.; Mokriienko, E.; Lazor, N. (Journal of Education, Health and Sport, 2023)
An urgent problem today is not only the study of changes in the stability of the genome of somatic cells, the clarification of the mechanisms of its destabilization under the influence of a complex of environmental factors, including radiation, but also the study of the possibility of hereditary transmission of these changes. In the modern experimental and clinical medicine, the most important problem is the harmful effect of ionizing radiation on the descendants of irradiated parents and the specifics of the effect of radiation on the developing organism. An important aspect of the problem of long-term post-radiation effects is the state of reproductive function and health of the descendants of the irradiated population, due to the physiological characteristics inherent to the mother and child - high sensitivity to the action of ionizing radiation, the consequences of which may manifest after a long period of imaginary well-being. The purpose of the work is to investigate the dynamics of body weight and hematological indiexes in the descendants of intact sexually mature animals and descendants born to animals irradiated at different doses, which were exposed to radiation at a dose of 1.0 Gy. The authors revealed that in descendants born to animals irradiated at different doses, which were exposed to radiation at a dose of 1.0 Gy, it was established that by the 30th day after irradiation at a dose of 1.0 Gy, the general condition of pup rats born from animals irradiated at a dose of 0.5 Gy and exposed to irradiation at a dose of 1.0 Gy is satisfactory against the background of an insignificant decrease in the body weight. This also applies to pup rats born to animals irradiated at a dose of 1.0 Gy, whose general condition slightly improves compared to the previous period of the study. The data obtained showed in the peripheral blood after 1 day in the descendants born to animals irradiated at a dose of 0.5 Gy, after irradiation at a dose of 1.0 Gy, a reduced content of hemoglobin and erythrocytes against the background of an increase in the content of platelets, leukocytes, lymphocytes and reticulocytes in comparison with non-irradiated animals, which was maintained throughout the experiment. Pronounced changes in hematological parameters were observed in the descendants born to animals irradiated at a dose of 1.0 Gy, which were exposed to total γ-irradiation at a dose of 1.0 Gy. The authors suppose their data are in favour of the pronounced adaptationof organisms’ regulatiory systems to ionizing irradiation effect that, firstly, outline the adaptative physiologcal mechanisms and, secondly, show the main launches of pathophysiologcial mechamisns in case of irradiation-induced hematological changes.